Prehypertension among 2.19 million adolescents and future risk for end-stage renal disease. Issue 6 (June 2017) - Leiba, Adi; Twig, Gilad; Vivante, Asaf; Skorecki, Karl; Golan, Eliezer; Derazne, Estela; Tzur, Dorit; Grossman, Ehud; Dichtiar, Rita; Kark, Jeremy D.; Shohat, Tamar
Abstract : Objective: Persistent hypertension in adulthood is a leading cause of end-stage renal disease (ESRD). Whether lower blood pressure (BP) values, in the range of prehypertension, are also associated with future occurrence of ESRD is unclear. Even less clear is the potential risk of early prehypertension appearing in adolescence. To address this question, we examined whether BP measurements in the prehypertensive range at age 16–19 years predict adult ESRD. Methods: Medical data on 2194 635 16–19-year-old adolescents examined for medical fitness prior to military service from 1977 to 2013 were linked to the Israeli ESRD registry in this nationwide population-based cohort study. Incident cases of ESRD were recorded. Survival models were applied. Results: During 35 007 506 person-years of follow-up (median follow-up 16.8 years), there were 690 ESRD cases, with an overall incidence rate of 1.97 cases per 100 000 person-years. Examinees with elevated BP readings in the prehypertensive range (BP between the 90th and 95th percentiles or between 120 and 139/80–89 mmHg) had increased incidence of ESRD with a hazard ratio of 1.32 (95% confidence interval, 1.11–1.58) adjusted for year of birth, age at examination, sex, BMI, education, socioeconomic status, and country of origin. Hypertension (BP above the 95th percentile or above 140/90 mmHg) was associated with a hazard ratio of 1.44 (95% confidence interval, 1.17–1.79). A spline model demonstrated a nadir of risk at SBP values as low as 94 mmHg. Conclusion: Asymptomatic, healthy adolescents with prehypertension have a 32% increased risk for subsequent ESRD, compared with adolescents with optimal BP. Abstract : Supplemental Digital Content is available in the text